CeO2:Mn3O4 Catalytic Micro-Converters Tuned for CH4 Detection Based on Catalytic Combustion under Real Operating Conditions - Cristian E. Simion (Materials, 2020)
Mesoporous CeO2:Mn3O4 materials (3:7 and 7:3 molar ratio) were prepared by co-precipitation and deposited as porous thick films over alumina (Al2O3) planar substrate provided with Pt meander. The aim was oriented towards detecting low levels methane (CH4) at moderate operating temperatures. Herein we demonstrated that the sensitivity of catalytic micro-converters (CMCs) towards a given peak of CH4 concentration corresponds to specific gas-surface interaction phenomena. More precisely, a transition from thermal conductivity to combustion rate is likely to occur when CMCs are operated under real atmospheric conditions (normal pressure, presence of relative humidity, and constant operating temperature). The response to CH4 was analyzed over different gas flows and different gas concentrations under the same operating regime. The materials were fully characterized by adsorption-desorption isotherms, H2-Temperature Programmed Reduction (H2-TPR), X-ray Diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Scanning Electron Microscopy (SEM), and Raman spectroscopies. Thus, the applicative aspect of using CeO2:Mn3O4 as moderate temperature CMC for CH4 detection is brought to the fore.